Traditions of «Honouring the Bookish» as Value Orientation in Modern Philological Education (Proceedings of Southern Federal University. Philology, 2020)
A thousand-year tradition of «honouring the bookish» is one of the most important components of the educational system and social enlightenment, which is moved, among other things, by intellectual and spiritual reflection of the educators Cyril and Methodius. However, despite the fact that the national holiday of Slavic Alphabet and Culture has been present for twenty years, in modern conditions of weakening the historical memory and the significance of Christianity, there is a serious lack of information about the lives and activities of Konstantin the Philosopher, Methodius and their followers in the spiritual life of Slavdom and establishment of Russian mentality. That is why the great educational endeavor of the brothers of Thessaloniki, appropriately valued only in modern times, requires support from educational systems. Elaborating the details of historical and cultural preconditions to the appearance of the first Slavic ABC books, Bible translations and their existence in the Slavic world is extremely important to the future teachers of the Russian language and literature, and especially in the conditions of wide spread misinformation and decreasing amount of academic hours for studying the disciplines of historical and linguistic sciences,which, in one way or another, touch upon the problems of the origin of the ancient literary and scriptory language of the Slavic and its establishment under the influence of Russian literary language. Such position presupposes the need of providing a number of scientific and educational events in association with Memorial Day of Slavic Teachers and other dates, dedicated to language and book-learning. These events aid to redeeming the lost educational opportunities in bachelors’ philological training, as they help to build up beneficial cultural, educational and spiritual space, which is based on the traditions of «honouring the bookish», dating back to the Slavic enlighteners. A seventeen-year experience of holding such events helps not only to generalize existing study material, but also to introduce a system of extracurricular communication among educators, students and schoolchildren, contributing to integration of educational and disciplinary processes with scientific research work.Key words: philological education, project activities, Day of Slavic Alphabet and Culture, enlightenment, Cyril and Methodius’ activities, Glagolic script, Cyrillic script.DOI 10.18522/1995-0640-2020-3-185-196